Karyotypic Analysis of Children with Disorders of Sex Development (DSD) at Children Hospital & ICH, Lahore - Sarah Khan, Areiba Haider, Raafea Tafweez (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of different karyotypes in children with DSD presented at The Children Hospital & ICH, Lahore Study design: Cross sectional analytical Place and Duration of Study: Department of Genetics, Children Hospital and ICH, Lahore, from Jan 2016 to June 2017. Methodology: The study was conducted on 83 adolescent children with any form of DSD after taking an informed consent. A detailed history was taken and sex of rearing was noted. Physical examination was done to know the morphological sex while karyotyping of all the cases was done for the confirmation of their genetic sex. All the findings were recorded on a predesigned proforma. The cases that have undergone any surgical correction procedure for genital ambiguity were excluded. Data was analyzed by SPSS 21. Results: Out of 83 cases, 27(32.5%) cases were reared as male at birth while 56(67.4%) were reared as female. Karyotypic analysis was done in all 83 cases. 27 cases who were reared as male, their karyotypic analysis of male sex of rearing showed a chromosomal compliment of 46XY in 25(92.5%), 46XX in 01(3.7%), 46XXY in 01(3.7%). Out of 56 cases of female sex of rearing, 45(80.3%) had 46XX karyotype 03(5.3%) had 46XY karyotype, 45X0 in 07(12.5%) and one case (1.7%) showed a XXX karyotype. Conclusion: To ensure the high-quality life for such an individual, there is an urgent need for correct sex assignment. Chromosomal analysis is important as a first step in determining an accurate genetic sex before the costly diagnostic tests and surgical procedure.